2005
DOI: 10.1080/00016470510030788
|View full text |Cite
|
Sign up to set email alerts
|

Men with hip fractures have poorer nutritional status and survival than women

Abstract: The higher mortality rate in men than in women after hip fracture may in part be explained by the poor nutritional status in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
(32 reference statements)
2
26
1
2
Order By: Relevance
“…Postfracture malnutrition has been associated with a wide variety of adverse outcomes, including increased risk of mortality [7], longer hospital stays [8], and impaired recovery of physical function [9]. Between 50% and 68% of hip fracture patients suffer from some form of postfracture malnutrition [8,10,11], with the most consistently identified areas of malnutrition being insufficient protein and total energy intakes.…”
Section: Introductionmentioning
confidence: 99%
“…Postfracture malnutrition has been associated with a wide variety of adverse outcomes, including increased risk of mortality [7], longer hospital stays [8], and impaired recovery of physical function [9]. Between 50% and 68% of hip fracture patients suffer from some form of postfracture malnutrition [8,10,11], with the most consistently identified areas of malnutrition being insufficient protein and total energy intakes.…”
Section: Introductionmentioning
confidence: 99%
“…ALB, PAB, and TRA are visceral proteins that have different half-lives, and therefore the levels may reflect the relative chronicity of a patient's clinical condition. The half-life is 20 d for ALB, 9 d for TRA, and 2 d for PAB [15]. Because of the short half-life, the level of PAB was too sensitive to reflect accurate changes in the protein-calorie condition.…”
Section: Discussionmentioning
confidence: 99%
“…During the later 1990s, attention shifted in an attempt to predict survival and functional outcomes based upon various factors, including not only the fracture but also characteristics of the patients themselves [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. These studies have suggested that survival and functional recovery could be correlated to factors such as chronological age, gender, pre-morbid health, and preoperative functional status.…”
mentioning
confidence: 96%